Obstetric outcome of in vitro fertilization pregnancies compared with normally conceived pregnancies. - Tan, S; Doyle, P; Campbell, S; Beral, V; Rizk, B; Brinsden, P; Mason, B; Edwards, R (1992)
OBJECTIVE: To compare the obstetric outcome of in vitro fertilization pregnancies with normally conceived pregnancies. STUDY DESIGN: The obstetric outcome of in vitro fertilization pregnancies achieved in 763 British residents at two in vitro fertilization clinics resulting in the births of 961 babies were compared by means of the relative risk statistic with a control group of naturally conceived primiparous pregnancies matched by maternal age and multiplicity of pregnancy. RESULTS: Twenty-five percent of in vitro fertilization pregnancies were multiple pregnancies. The incidence of singleton term breech presentation was similar to that among controls. As compared with controls there was an increased incidence among in vitro fertilization pregnancies of vaginal bleeding and hypertension requiring hospitalization (p less than 0.001) and cesarean births (p less than 0.001) and, among in vitro fertilization singleton pregnancies, an increased incidence of intrauterine growth retardation (p less than 0.05), placenta previa (p less than 0.05), and preterm delivery (p less than 0.001). The congenital malformation, stillbirth, and perinatal mortality rates were comparable with maternal age-standardized national rates. CONCLUSIONS: Although the majority of in vitro fertilization pregnancies have a satisfactory obstetric outcome, there are a number of increased obstetric risks that may reflect the history of infertility, the relatively high incidence of poor obstetric history, and the lower threshold for obstetric intervention in in vitro fertilization patients.